2010
DOI: 10.1002/hyp.7872
|View full text |Cite
|
Sign up to set email alerts
|

Flow dynamics of groundwater and soil water in the former heap Gessenhalde at the uranium mining area of Ronneburg: a stable isotope approach

Abstract: The transit time of groundwater in the rapid flow area is less than 6 months, whereas water in the stagnant zone is stored for at least 1 year. In soil water, a clear response to different input signals is detectable only in the 30-cm horizon (retention time is about 6 months), whereas at deeper levels a mixing with older water is taking place. The isotopic composition of the dissolved sulphate was used to identify oxidation of sulphides as the source of sulphate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This is likely due to the presence of larger pores from developed root systems, which facilitated the generation of preferential flow. Vegetation coverage and human disturbance in shrubland enhances soil compaction and reduces the number of macropores; this slows the rate of precipitation infiltration, resulting in the dominance of plug flow [20,61]. Yu et al [62] identified infiltration coefficients of 0.91, 0.64, and 0.74 in shifting dunes, shrub-dominated communities, and herb-dominated communities, respectively.…”
Section: Influence Of Stand Type On Soil Water Stable Hydrogen and Oxygen Isotopesmentioning
confidence: 99%
“…This is likely due to the presence of larger pores from developed root systems, which facilitated the generation of preferential flow. Vegetation coverage and human disturbance in shrubland enhances soil compaction and reduces the number of macropores; this slows the rate of precipitation infiltration, resulting in the dominance of plug flow [20,61]. Yu et al [62] identified infiltration coefficients of 0.91, 0.64, and 0.74 in shifting dunes, shrub-dominated communities, and herb-dominated communities, respectively.…”
Section: Influence Of Stand Type On Soil Water Stable Hydrogen and Oxygen Isotopesmentioning
confidence: 99%